2016
DOI: 10.1159/000444078
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin in Heart Failure with a Reduced Ejection Fraction: A Risk Factor or a Risk Marker?

Abstract: Digoxin is one of the oldest compounds used in cardiovascular medicine. Nevertheless, its mechanism of action and most importantly its clinical utility have been the subject of an endless dispute. Positive inotropic and neurohormonal modulation properties are attributed to digoxin, and it was the mainstay of heart failure therapeutics for decades. However, since the institution of β-blockers and aldosterone antagonists as part of modern heart failure medical therapy, digoxin prescription rates have been in fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 646 publications
(25 citation statements)
references
References 84 publications
1
21
0
1
Order By: Relevance
“…Our study confirms the findings of several authors [3-7, 12, 17, 18] who showed a negative influence of digoxin on the outcomes of HF patients, and contradicts others who showed a neutral [9,19] or a positive effect of digoxin [2,10,[20][21][22][23]. Our analysis suggests that worse clinical state of patients treated with digoxin might be at least partially responsible for the observed association with increased risk of death, which was mentioned earlier by only a few authors [24,25]. To our knowledge, this is the first study including patients who received the guideline-directed treatment (b-blockers 91.9%, ACEI or ARB 89.6%, and MRA 69.4%) and who were treated with digoxin throughout the follow-up period.…”
Section: Key Findingssupporting
confidence: 90%
“…Our study confirms the findings of several authors [3-7, 12, 17, 18] who showed a negative influence of digoxin on the outcomes of HF patients, and contradicts others who showed a neutral [9,19] or a positive effect of digoxin [2,10,[20][21][22][23]. Our analysis suggests that worse clinical state of patients treated with digoxin might be at least partially responsible for the observed association with increased risk of death, which was mentioned earlier by only a few authors [24,25]. To our knowledge, this is the first study including patients who received the guideline-directed treatment (b-blockers 91.9%, ACEI or ARB 89.6%, and MRA 69.4%) and who were treated with digoxin throughout the follow-up period.…”
Section: Key Findingssupporting
confidence: 90%
“…Digoxin was the cornerstone for decades to antagonize systolic left ventricularimpairments [34] . Subsequently, the use of digoxin is constantly declined for the uncertain regarding its clinical efficacy and the risks associated with long-term digoxin use, presumably d dependent on its pro-arrhythmic properties [35][36][37] .…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Valsartan does not inhibit Digoxin is the oldest cardiac drug still in contemporary use, and can be useful in patients with persistent severe end-stage HF (LVEF <25%, cardiothoracic ratio >55%, New York Heart Association (NYHA) class III or IV) undergoing guideline-directed medical therapy, and especially symptomatic patients being treated with neurohormonal antagonists [13]. Digoxin has been used as the first line of pharmacological treatment for HF until the understanding of HF pathophysiology changed in recent decades, which leads to the shift from inotropic support to neurohormonal modulation [14]. The effect is regardless of the rhythm, etiology of HF, or concomitant therapy.…”
Section: Cardiomyopathies -Types and Treatments 412mentioning
confidence: 99%
“…Digoxin has been used as the first line of pharmacological treatment for HF until the understanding of HF pathophysiology changed in recent decades, which leads to the shift from inotropic support to neurohormonal modulation [14]. The effect is regardless of the rhythm, etiology of HF, or concomitant therapy.…”
Section: Cardiomyopathies -Types and Treatmentsmentioning
confidence: 99%